Health Indices in South Asian Countries: Time Series Analysis (2005-2013) - Rehman, Adeela; Mohamad Diah, Nurazzura (2015)
Objectives: To explore the South Asian region low health conditions with respect to maternal and child healthcare. Due to lack of resources, poverty, socio-economic and cultural factors; hence, the maternal and child mortality index in this region is rather unsatisfactory. Comparison of different countries depicts that it is hard to achieve the full targets and goals to reduce mortality, but progress in minimizing mortality rates in all South Asian countries is on-going. Design: Time Series Analysis. Setting: Health Indices of selected South East Asian countries over nine years from 2005 to 2013. Countries: The countries include Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. Results: The analysis indicates that all countries are continuously struggling to reduce the number of mother and child deaths by adopting multiple national and international policies, programmes and strategies. The time series graph of each country on multiple indexes shows the continuous progress of each country. Among those, Sri Lanka is at the best position by having the lowest number of maternal and child mortality compared to the other seven countries. India and Pakistan are at the critical position of mortality as they have larger populations than other South Asian countries and have limited resources, but still positive progress is going to limit the mortality ratios. Conclusion: It is concluded that as these nations’ development and health status rely very much on the mothers’ and children’s survival, efforts to reduce mortality rates should be continued to achieve the developmental goals.